Gender Equality In Katja Von Garnier's Iron Jawed Angel (2004): A Feminist Perspective - Alimah, Kun; , Drs. Abdillah Nugroho, M.Hum; , Titis Setyabudi, S.S M.Hum (2013)
The research paper is aimed at analyzing Gender Equality in Katja Von Garnier‟s Iron Jawed Angel's movie. The research analyze how is the struggle to get gender equality reflected in Katja Von Garnier‟s Iron Jawed Angels movie based on a feminist perspective. It occurs because there is some evidence that support equality gender. The objective of this research paper is to analyze the film in terms of its structural element based on a feminist perspective. The researcher employs qualitative research method. In this method, the researcher uses two data resources namely primary and secondary data sources. The primary data source is the film of Katja Von Garnier‟s Iron Jawed Angels itself. The secondary data source taken from some reference and material related to the study whether by picking up from books and internet. The method of data collection is library research and the technique of data analysis. The feminist analysis has close relation between products of this film, Iron Jawed Angels, and the social realities of American Society in 1920s. The focus of politic aspect is supporting the gender equality. The right for woman to vote is needed to help women in enjoying their lives. The writer hopes to understand that man and woman are equal and of course woman needs right to protect her life.